2013
DOI: 10.1016/j.neuron.2013.06.038
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Gradient along the Dorsoventral Axis in the Medial Entorhinal Cortex

Abstract: Local inhibitory microcircuits in the medial entorhinal cortex (MEC) and their role in network activity are little investigated. Using a combination of electrophysiological, optical, and morphological circuit analysis tools, we find that layer II stellate cells are embedded in a dense local inhibitory microcircuit. Specifically, we report a gradient of inhibitory inputs along the dorsoventral axis of the MEC, with the majority of this local inhibition arising from parvalbumin positive (PV+) interneurons. Final… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
114
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(128 citation statements)
references
References 41 publications
11
114
3
Order By: Relevance
“…Mechanisms underlying hyperexcitability of neurons in superficial MEA seem to be layer-specific: while LII stellate cells are rendered hyperexcitable because of reduced inhibition, LIII pyramidal neurons are rendered hyperexcitable on account of enhanced excitation. The apparent distinction in how alterations in synaptic drive mediate hyperexcitability of these neurons complements the observation that under normal conditions, inhibitory synaptic drive in LII stellate cells is significantly greater than in LIII pyramidal neurons (Beed et al 2013;Couey et al 2013), as confirmed in our recordings of baseline synaptic drive to these neurons in control animals. Previous studies have proposed synaptic reorganization of PrS afferents contacting surviving neurons in LIII and neighboring LII following loss of LIII neurons as a potential mechanism for MEA hyperexcitability (Scharfman et al 1998;Tolner et al 2005).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Mechanisms underlying hyperexcitability of neurons in superficial MEA seem to be layer-specific: while LII stellate cells are rendered hyperexcitable because of reduced inhibition, LIII pyramidal neurons are rendered hyperexcitable on account of enhanced excitation. The apparent distinction in how alterations in synaptic drive mediate hyperexcitability of these neurons complements the observation that under normal conditions, inhibitory synaptic drive in LII stellate cells is significantly greater than in LIII pyramidal neurons (Beed et al 2013;Couey et al 2013), as confirmed in our recordings of baseline synaptic drive to these neurons in control animals. Previous studies have proposed synaptic reorganization of PrS afferents contacting surviving neurons in LIII and neighboring LII following loss of LIII neurons as a potential mechanism for MEA hyperexcitability (Scharfman et al 1998;Tolner et al 2005).…”
Section: Discussionsupporting
confidence: 80%
“…Alterations in release probability potentially influence spontaneous synaptic activity, but baseline sEPSC frequency for LII stellate cells in epileptic rats was similar to controls. Besides altered release probability, changes in calcium buffering and signal integration properties (Blitz et al 2004;Regehr 2012) may also contribute to increased paired-pulse facilitation in LII stellate cells under epileptic conditions. The large-amplitude epileptogenic events observed in LII and LIII neurons following PrS stimulation exclusively in epileptic rats likely reflect network hyperexcitability and hypersynchrony within the MEA (Bragin et al 1999;Kumar and Buckmaster 2006), similar to PrS-triggered aberrant MEA activity described previously (Scharfman et al 1998;Tolner et al 2007;Tolner et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…PV interneurons differentially target stellate cells along the D/V axis of mEC. Dorsal stellate cells receive a greater number of and more widespread PV inhibitory synaptic contacts compared to ventral stellate cells (Beed et al, 2013). The stronger inhibition in dorsal stellates could lead to faster rebound spiking and smaller spacing between grid cell firing fields compared to ventral stellate cells.…”
Section: Discussionmentioning
confidence: 99%
“…Extracellular recordings indicate that grid cells occupy modules with similar spatial scales Stensola et al, 2012) that exhibit strong relative spatial stability even when unstable with respect to the environment (Yoon et al, 2013). The density of grid cells is highest in mEC layer II, where they appear to be stellate and pyramidal cells (Domnisoru et al, 2013) with relatively few monosynaptic excitatory interactions but significant disynaptic recurrent inhibitory connectivity (Dhillon and Jones, 2000;Beed et al, 2010;Quilichini et al, 2010;Beed et al, 2013;Couey et al, 2013;Pastoll et al, 2013). These properties are consistent with CAN models of grid cell firing (Fuhs and Touretzky, 2006;McNaughton et al, 2006;Guanella et al, 2007;Burak and Fiete, 2009;Pastoll et al, 2013).…”
Section: Can Dynamicsmentioning
confidence: 99%